2013
DOI: 10.1371/journal.pone.0073471
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polychlorinated Biphenyls on the Song of Two Passerine Species

Abstract: Polychlorinated biphenyls (PCBs) are synthetic chemical pollutants with demonstrated detrimental toxic and developmental effects on humans and wildlife. Laboratory studies suggest that PCBs influence behavior due to their effects on endocrine and neurological systems, yet little is known about the behavioral consequences of sublethal PCB exposure in the field. Additionally, specific PCB congener data (in contrast to total PCB load) is necessary to understand the possible effects of PCBs in living organisms sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Hoogesteijn et al found reduced volumes of the song control nucleus robustus arcopallialis in the brains of juvenile zebra finches after exposing the maternal hens to just 40 μg Aroclor 1248, which for a typical 12‐g finch is equivalent to 3.3 μg Aroclor 1248/g body weight (measured egg concentrations = 0.19 μg/g wet w). A study from the historically PCB‐contaminated region of the Hudson River revealed that black‐capped chickadees ( Poecile atricapillus ) and song sparrows ( Melospiza melodia ) in the affected area had higher blood PCBs and altered song profiles . Possibly most compelling is that the present study extends from research on the same set of dosed starlings tested previously in an autumn migratory experiment, which were found to have impaired migratory orientation ability .…”
Section: Discussionsupporting
confidence: 58%
“…Hoogesteijn et al found reduced volumes of the song control nucleus robustus arcopallialis in the brains of juvenile zebra finches after exposing the maternal hens to just 40 μg Aroclor 1248, which for a typical 12‐g finch is equivalent to 3.3 μg Aroclor 1248/g body weight (measured egg concentrations = 0.19 μg/g wet w). A study from the historically PCB‐contaminated region of the Hudson River revealed that black‐capped chickadees ( Poecile atricapillus ) and song sparrows ( Melospiza melodia ) in the affected area had higher blood PCBs and altered song profiles . Possibly most compelling is that the present study extends from research on the same set of dosed starlings tested previously in an autumn migratory experiment, which were found to have impaired migratory orientation ability .…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, sexually dimorphic behaviors were altered in rats exposed to PCBs (Lilienthal et al, 2013). Adverse effects of PCB exposure on reproductive and thyroid systems as well as singing behavior have been observed in birds (Deleon et al, 2013; Ottinger et al, 2013). Other effects, including impaired cardiac development, which may reflect early impacts on growth factors, have the potential to greatly diminish the fitness of the individual (Carro et al, 2013).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…We found that timing of exposure is important, and the in ovo stage appears to be a more sensitive window than the early post-hatch period with respect to the effects on the song-control system from organohalogen contaminant exposure. The present study contributes to the increasing evidence that studying the song-control system and could be a sensitive tool for assessing impacts of environmental contaminants (Gorissen et al, 2005;Iwaniuk et al, 2006;Hoogesteijn et al, 2008;Markman et al, 2008;McKay and Maher, 2012;DeLeon et al, 2013). Effects on song learning and production could also potentially serve as a link between contaminant exposure and effects that are relevant for ecological risk assessment, such as reproductive and population level effects.…”
Section: Resultsmentioning
confidence: 78%